FEM-DEM simulation of Brazilian Tensile Strength (BTS) laboratory tests - Michel Melo Oliveira; Cláudio Lúcio Lopes Pinto; Douglas Batista Mazzinghy (REM: International Engineering Journal, 2021)
Abstract A Brazilian Tensile Strength (BTS) laboratory test for meta-andesite was modeled using a Finite/Discrete Element Method (FDEM or FEM-DEM). These hybrid methodologies allow modeling the transition from continuous to discontinuous that happens on mechanical tests of rock samples. This article presents the calibration and the simulation of BTS tests using some parameters previously calibrated on UCS modeling of the same material. Irazu, a two-dimensional software developed by Geomechanica, was used to simulate the tests based on the tensile strength and the fracture pattern. The model shows that, in BTS test simulation, the mode II (shear) happens mainly on the rock-platen contact. The mode I (traction) rules the fractures on the BTS test as observed in laboratory tests. The model represents, with great fidelity, the results obtained in the physical test.